2022
DOI: 10.1057/s41599-022-01070-2
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of translating health research findings into policy in sub-Saharan Africa: A Scoping Review

Abstract: Despite efforts made by sub-Saharan Africa (SSA) countries to promote evidence-informed health policymaking, translating research evidence into policy remains a very challenging task fraught with many barriers. However, to achieve the goal of making more evidence-informed decisions to improve health, it is critical to overcome the barriers to the translation of research into policy. This paper provides an overview of the barriers and facilitators of translating research into policy in SSA countries to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…But the "research to policy gap" represents a significant impediment to translating scientific knowledge about evidence-based practices (EBPs) into public policy, limiting widespread improvements in service and population health outcomes [1]. Common barriers to translating research into health policy include weak relationships between the producers and users of research, poor alignment between research questions and policymaker priorities, and untimely and inadequate dissemination of research in accessible language and formats [1][2][3][4]. Complex political contexts where partisan ideologies, advocacy interests, and budgetary and resource constraints interact also impact the degree to which policy is informed by research findings [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…But the "research to policy gap" represents a significant impediment to translating scientific knowledge about evidence-based practices (EBPs) into public policy, limiting widespread improvements in service and population health outcomes [1]. Common barriers to translating research into health policy include weak relationships between the producers and users of research, poor alignment between research questions and policymaker priorities, and untimely and inadequate dissemination of research in accessible language and formats [1][2][3][4]. Complex political contexts where partisan ideologies, advocacy interests, and budgetary and resource constraints interact also impact the degree to which policy is informed by research findings [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This could also explain why the participants considered the current evidence used to be relevant. Additionally, the weak researcher–policy-maker linkage further hampers the use of evidence from external academic institutions [ 24 , 37 ]. In contrast, another study among Nigerian health policy-makers showed that the participants used survey reports and research publications external to the institution such as Lancet papers in the issue-raising phase of policy-making [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Partnerships between researchers and policy-makers have been found to be suboptimal, with many identified barriers to effective knowledge translation and use of research evidence in decision-making by policy-makers. [ 21 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among researchers identified EIDM capacity constraints include lack of knowledge about what knowledge translation (KT) is and how to do it, lack of soft skills for navigating the complex policy processes, misalignment between institutional missions and incentives for researchers and policymakers, and insufficient institutional resources (e.g., financing and time), support (e.g. staff and training), leadership and external and internal networks (9,(11)(12)(13).…”
Section: Strengthening Institutional Eidm Capacity In Low-and Middle-...mentioning
confidence: 99%